2015
DOI: 10.5114/kitp.2015.52867
|View full text |Cite
|
Sign up to set email alerts
|

CASE REPORTS Echocardiographic diagnosis of a massive left ventricular pseudoaneurysm: a case report

Abstract: Left ventricular aneurysm is one of the most troublesome complications of myocardial infarction. This complication results from LV wall rupture and presents as a cavity contained by pericardium and fragments of the ruptured wall. The risk of pseudoaneurysm rupture is very high and this makes the prognosis for the disease extremely unfavorable. A surgical correction, involving a patch repair of the LV wall, seems to be the only treatment modality. Echocardiography makes it possible to diagnose pseudoaneurysm of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…3D). Sokolskaya et al reported the usefulness of echocardiography for the preoperative and postoperative assessment of LV pseudo-aneurysms (5). After the diagnosis of LV pseudo-aneurysm is made, treatment options should be discussed.…”
Section: Discussionmentioning
confidence: 99%
“…3D). Sokolskaya et al reported the usefulness of echocardiography for the preoperative and postoperative assessment of LV pseudo-aneurysms (5). After the diagnosis of LV pseudo-aneurysm is made, treatment options should be discussed.…”
Section: Discussionmentioning
confidence: 99%
“…TTE, CT, MRI and ventricular angiography can be used for diagnostic imaging [ 6 7 8 9 ]. The most reliable method for diagnosing LVFA is angiography, but TTE is a useful first step [ 2 10 11 ]. Distinguishing a false aneurysm from a true aneurysm is important because treatment strategies for the two differ vastly.…”
Section: Discussionmentioning
confidence: 99%